Growth factor receptor plasticity drives therapeutic persistence of metastatic breast cancer - Mitchell Ayers; Marvis Monteiro; Aneesha Kulkarni; Julie W. Reeser; Emily Dykhuizen; Sameek Roychowdhury; Michael K. Wendt (Cell Death and Disease)
Abstract Metastatic breast cancer (MBC) remains a therapeutic challenge due to the persistence of minimal residual disease (MRD) and tumor recurrence. Herein we utilize a model of MBC that is sensitive to inhibition of fibroblast growth factor receptor (FGFR), resulting in robust regression of pulmonary lesions upon treatment with the FGFR inhibitor pemigatinib. Assessment of the remaining MRD revealed upregulation of platelet-derived growth factor receptor (PDGFR). Functionally, we demonstrate increased response to PDGF ligand stimulation following pemigatinib treatment. Depletion of PDGFR did not alter tumor growth under control conditions but did delay tumor recurrence following a treatment window of pemigatinib. To overcome this therapeutic hurdle, we found that inhibition of DNA methyltransferase 1 (DNMT1) prevents pemigatinib-induced cellular plasticity. Combined targeting of FGFR and DNMT1 prevented induction of PDGFR, enhanced pulmonary tumor regression, slowed tumor recurrence, and prolonged survival. These findings enhance our understanding of cellular plasticity during states of treatment-induced MRD and suggest that inhibition of DNA methylation could augment current approaches being used to treat MBC.